A cyclic heat treatment organization regulation method for LPBF additive manufacturing of TC11 titanium alloy and application thereof

CN122918480APending Publication Date: 2026-10-16WUHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611287476.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

该针状α′马氏体属于非平衡相,其内部存在高密度缺陷和元素偏析,导致打印态材料呈现高强度但低塑性、各向异性显著等问题,限制了构件的工程应用

Benefits of technology

(1)本发明提供的一种LPBF增材制造TC11钛合金的循环热处理组织调控方法,通过双温区多次循环热处理,利用α/β界面反复迁移和相变应力的累积效应,使激光粉末床熔融成形TC11钛合金打印态组织中的非平衡α′马氏体组织逐步发生分解、切割、短化和球化,有效解决了单次退火或固溶处理中组织粗化、组织遗传明显的问题。根据T1温度的选择,本发明提供了两条调控路线:双相区循环(T1、T2均位于α+β双相区内)可获得细小均匀的等轴α+β组织,有效减少连续晶界α,改善组织均匀性和各向同性;跨相区循环(T1高于β转变温度,T2位于α+β双相区内)可获得网篮状α+β组织,破坏原始板条结构并促进多取向α片层重新析出。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918480A_ABST
    Figure CN122918480A_ABST
Patent Text Reader

Abstract

The application provides a cyclic heat treatment microstructure regulation method for LPBF additive manufacturing of TC11 titanium alloy and application thereof. The method comprises the following steps: providing a laser powder bed fusion formed TC11 titanium alloy printed part, the microstructure of the printed part comprising alpha prime martensite; placing the printed part at a first temperature T1 for heat preservation, so that part or all of the alpha prime martensite is decomposed and beta phase is formed; placing the printed part at a second temperature T2 for heat preservation, so that the beta phase is re-precipitated into alpha phase; repeating the above cycle n times, and then air cooling to room temperature, and then performing aging treatment; wherein T1>T2, T2 is located in an alpha+beta dual-phase region, and T1 is located in the alpha+beta dual-phase region or is higher than a beta transition temperature. Through multiple cycles, the alpha / beta interface is repeatedly migrated, so that the printed state microstructure is gradually transformed into fine and uniform equiaxed alpha+beta microstructure or net basket-shaped alpha+beta microstructure, and the different requirements for microstructure uniformity, high-temperature performance and wear resistance under different service conditions can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of titanium alloy additive manufacturing post-processing and metal heat treatment technology, specifically involving a method for controlling the cyclic heat treatment of TC11 (α+β type) titanium alloy printed microstructure by laser powder bed melting / selective laser melting and its application. Background Technology

[0002] TC11 titanium alloy belongs to the α+β type high-temperature titanium alloy, possessing high specific strength, high thermal strength, and good overall service potential. When TC11 components are fabricated using additive manufacturing methods such as laser powder bed melting, the material undergoes rapid melting, rapid solidification, and interlayer thermal cycling. The printed microstructure is typically dominated by acicular or lamellar α′ martensite, accompanied by varying degrees of original β grains, melt pool boundaries, and microstructure inheritance characteristics. This acicular α′ martensite is a non-equilibrium phase, containing high-density defects and elemental segregation, leading to problems such as high strength but low plasticity and significant anisotropy in the printed material, limiting the engineering applications of the components.

[0003] Existing simple annealing or single solution / solution aging treatments can promote the decomposition of α′ martensite, release residual stress, and form α+β microstructure, but still have the following shortcomings: First, low-temperature annealing has limited effect on cutting and isoaxializing the original slender lamellars, and retains more of the microstructure's genetic characteristics; second, higher temperature solution treatments easily lead to the merging, growth, and local coarsening of α lamellars, weakening interfacial strengthening; third, a single heat treatment only involves one phase transformation process, making it difficult to simultaneously achieve microstructure refinement, homogenization, α / β interface regulation, and hardness strengthening response.

[0004] Cyclic heat treatment can be summarized as setting multiple heat treatment temperature zones above the martensite decomposition temperature, near the β transformation temperature, or between the β phase region and the α+β phase region. Through heating and holding, controlled cooling and holding, and repeated cycles, the microstructure gradually evolves towards equiaxed crystals, short rod-shaped α phases, or basket-like α+β microstructures during repeated phase transformations. However, existing cyclic heat treatment schemes are mostly generalized descriptions or only applicable to other titanium alloy grades (such as TC4), failing to consider the correlation between the elemental distribution behavior of Mo, Zr, and Si in TC11 alloy and the specific decomposition mechanism of α′ martensite in additive manufacturing, and lacking a systematic cyclic regime design for the microstructure of TC11 in additive manufacturing.

[0005] Therefore, how to effectively control the α-phase morphology through heat treatment in the printed microstructure of TC11 titanium alloy in additive manufacturing, in order to obtain TC11 titanium alloy components with uniform microstructure and stable performance, is a technical problem that urgently needs to be solved in this field. In particular, how to selectively obtain equiaxed or basket-net microstructures to meet differentiated performance requirements for different service conditions is currently lacking a systematic solution. Summary of the Invention

[0006] One objective of this invention is to provide a cyclic heat treatment microstructure control method for LPBF additive manufacturing of TC11 titanium alloy. By inducing repeated migration of the α / β phase interface through multiple temperature cycles, the α′ martensite microstructure in the printed state undergoes decomposition, cutting, shortening, spheroidization, or basket-like reconstruction, resulting in TC11 titanium alloy components with uniform microstructure and controllable properties. This improves upon the problems of microstructure coarsening, obvious microstructure inheritance, and insufficient strength-plasticity matching in conventional single annealing or solution treatment.

[0007] The second objective of this invention is to provide an application of the above-mentioned cyclic heat treatment microstructure control method in the preparation of TC11 titanium alloy components.

[0008] One of the technical solutions adopted by this invention to achieve its objective is to provide a method for controlling the microstructure of TC11 titanium alloy through cyclic heat treatment in additive manufacturing, characterized by comprising the following steps: S1. Provide a TC11 titanium alloy printed part formed by laser powder bed melting, wherein the microstructure of the TC11 titanium alloy printed part includes α′ martensite; S2. The TC11 titanium alloy printed part is kept at a first temperature T1 to cause some or all of the α′ martensite to decompose and form the β phase. S3. The TC11 titanium alloy printed part after S2 is placed at a second temperature T2 and kept at that temperature to allow the β phase to re-precipitate into the α phase. S4. Repeat steps S2 and S3 a total of n times, where n≥2; S5. Air cool the TC11 titanium alloy printed part after step S4 to room temperature. Wherein, T1 > T2, T2 is within the α+β dual-phase temperature range of TC11 titanium alloy, and T1 is within the α+β dual-phase temperature range of TC11 titanium alloy or higher than the β transformation temperature of TC11 titanium alloy.

[0009] The overall concept and inventive principle of this invention are as follows: Unlike the microstructure of forged TC11 (which is usually an equiaxed α+β bimodal microstructure or Widmanstätten microstructure), the microstructure of laser powder bed melting (LPBF) formed TC11 titanium alloy in the printed state has the following characteristics: (1) it is dominated by fine needle-like non-equilibrium α′ martensite; (2) it has coarse columnar β grains and molten pool boundaries; (3) it has obvious microstructure inheritance characteristics. The above characteristics lead to the problem that printed TC11 has high strength but low plasticity and significant anisotropy. Its heat treatment response is fundamentally different from that of forged TC11, and conventional heat treatment regimes designed for forging cannot be directly applied.

[0010] This invention addresses the presence of a large amount of non-equilibrium α′ martensite in the printed microstructure of TC11 titanium alloy formed by LPBF, proposing a method to achieve controllable microstructure reconstruction through multiple temperature cycles. The core idea is to utilize the reversible phase transformation characteristics of TC11 titanium alloy in the α+β dual-phase and β-phase regions. By setting a first temperature T1 and a second temperature T2, the printed microstructure undergoes a phase transformation process of "α → partial or complete dissolution to form β → β to α re-precipitation" in each cycle. Through repeated migration of the α / β interface and phase transformation stress accumulated over multiple cycles, the original slender lamellar layers are gradually reconstructed by cutting, shortening, spherizing, or basket-like shaping.

[0011] Depending on the temperature range in which T1 is located, this invention provides two optional control routes: Route 1: Cyclic Heat Treatment in the Two-Phase Region. Both T1 and T2 are set within the α+β two-phase region temperature range of the TC11 titanium alloy (T1 > T2). During the T1 holding stage, some α / α′ lamellae dissolve and form the β phase at the lamellar interface; after transferring to T2 holding, the β phase reprecipitates towards the α phase, inducing α / β interface migration. After multiple cycles, interfacial diffusion induces a thermal grooving effect, causing boundary splitting of the original long lamellae, reducing the aspect ratio of the α lamellae, increasing multi-oriented α nucleation, and ultimately forming a fine and uniform equiaxed α+β microstructure. This route is suitable for service conditions requiring high microstructure uniformity and isotropy.

[0012] Route 2: Transphase Region Cyclic Heat Treatment. Temperature T1 is higher than the β transformation temperature of TC11 titanium alloy (located in the β single-phase region), while T2 falls within the α+β two-phase region temperature range. During the T1 holding stage, the original α / α′ lamellae largely or completely dissolve to form a single β phase; after the T2 holding stage, the β phase reprecipitates towards the α phase, forming multi-oriented interlaced α lamellae. After multiple cycles, the original lath structure is destroyed, ultimately forming a basketweave α+β microstructure. This route is suitable for service conditions requiring high-temperature creep strength, creep resistance, and fracture toughness.

[0013] The two routes can be flexibly selected according to the target performance and application requirements. After the cycle is completed, the system is air-cooled to room temperature and can be further subjected to aging treatment to promote the precipitation of fine secondary α phases and enhance the hardness strengthening response.

[0014] Furthermore, for the two-phase region cyclic heat treatment, T1 is 950-990℃ with a holding time of 10-30 min; T2 is 830-870℃ with a holding time of 10-30 min; and n is 3-5. Controlling the holding time to 10-30 min allows for sufficient local dissolution and interfacial migration of the α' martensite structure in the T1 stage, while avoiding excessively long holding times that could lead to α-lamellae coalescence, coarsening, or abnormal grain growth. Preferably, T1 is 980±10℃ with a holding time of 20±5 min; and T2 is 850±10℃ with a holding time of 20±5 min. Studies have shown that in the two-phase region cyclic heat treatment, the aspect ratio of the lamellar α-structure first decreases and then increases with the number of cycles, reaching its minimum value when n=4.

[0015] Furthermore, for the cross-phase region cyclic heat treatment, T1 is 1010-1030℃ with a holding time of 5-15 min; T2 is 920-940℃ with a holding time of 20-40 min; and n is 4-10. The 5-15 min holding time in T1 allows the original α' martensite to fully dissolve into the β phase and avoids excessive β grain growth due to prolonged high-temperature holding. The 20-40 min holding time in T2 provides sufficient diffusion time for the β phase to redefine the α lamellae towards multiple orientations, thus forming a basketweave α+β structure, while also preventing lamellar coarsening due to excessively long holding times. In addition, studies have found that with increasing cycle count, the redistribution of β-stabilizing elements (such as Mo, Zr, and Si) is more complete, the residual β phase content gradually increases, and the macroscopic hardness shows an upward trend; however, when the number of cycles reaches 10, the α lamellae become significantly coarser, the interlamellar spacing increases, and the microstructure begins to evolve in a coarsening direction. In summary, a cycle count of 5 times can achieve good microstructure refinement while maintaining the basketweave microstructure characteristics; a cycle count of 10 times can achieve a higher hardness strengthening response, but too many cycles may lead to β grain growth, lamellar coarsening and residual β continuity. Therefore, the number of cycles should be reasonably controlled and should not exceed 10 times.

[0016] Furthermore, steps S2 and S3 are performed in different heating furnaces. This invention employs a dual-furnace transfer strategy, rapidly transferring the TC11 titanium alloy printed part between two isothermal platforms. This significantly reduces the processing time of the cyclic heat treatment, lowers energy consumption, and the rapid cooling also inhibits the continuous coarsening of the α-lamellae during the cooling process, enhancing the equiaxed trend. Specifically, in step S3, the TC11 titanium alloy printed part treated in step S2 is transferred from a heating furnace at the first temperature T1 to another heating furnace preheated to the second temperature T2, with a transfer time not exceeding 1 minute. The purpose of rapid transfer is to avoid uncontrollable phase transformations or premature precipitation of the α-phase at intermediate temperatures, ensuring that the microstructure transformation is mainly dominated by the holding process at temperature T2, thereby guaranteeing the consistency of the phase transformation path and interface migration conditions in each cycle.

[0017] Furthermore, steps S2 and S3 are performed in an air atmosphere. Compared to heat treatment under vacuum or inert gas protection, operation in an air atmosphere does not require special atmosphere protection equipment, the process is simple and low-cost, and it is suitable for industrial mass production.

[0018] Furthermore, step S5 also includes: aging the TC11 titanium alloy printed part after air cooling to room temperature at a temperature of 520-540 ℃ for 5-7 hours. After cyclic heat treatment, some metastable β phases are retained in the microstructure. The aging treatment promotes the decomposition of these metastable β phases into fine and dispersed secondary α phases. The resulting precipitation strengthening effect can further enhance the hardness of the alloy and improve its mechanical properties.

[0019] The second objective of this invention is to provide the application of the method described in one objective in the preparation of TC11 titanium alloy components.

[0020] Furthermore, the method is used to transform the α′ martensite in the TC11 titanium alloy printed part into a fine and uniform equiaxed α+β microstructure. Preferably, when a fine and uniform equiaxed α+β microstructure is required, a two-phase cyclic heat treatment scheme is adopted: the printed part is placed at 980 °C for 20 min to dissolve some of the α′ martensite and form the β phase; then it is transferred to 850 °C for 20 min to allow the β phase to reprecipitate into the α phase; this cycle is repeated 4 times and then air-cooled to room temperature. After this treatment, the α′ martensite in the printed microstructure is fully cut and transformed into a smaller, uniformly distributed equiaxed α+β microstructure, the continuous grain boundary α is reduced, and the equiaxing and grain refinement effects are significant. This scheme is suitable for service conditions with high requirements for microstructure uniformity and isotropy, such as compressor disks and structural frames for aerospace applications.

[0021] Furthermore, the method is used to transform the α′ martensite and / or lamellar α structure in the printed TC11 titanium alloy part into a basket-weave α+β structure. Preferably, when a basket-weave α+β structure is required, a cross-phase cyclic heat treatment scheme is adopted: the printed part is placed at 1020 °C for 10 min to completely dissolve the α′ martensite and form the β phase (at this temperature, the temperature is higher than the β transformation temperature of TC11 titanium alloy); then it is transferred to 930 °C for 30 min to allow the β phase to reprecipitate into the α phase; this cycle is repeated 5 times and then air-cooled to room temperature. After this treatment, the microstructure is dominated by multi-oriented interlaced α lamellars, forming a distinct basket-weave structure, and the residual β phase content is increased compared to the two-phase cyclic treatment. This scheme is suitable for service conditions with high requirements for high-temperature creep strength, creep resistance, and fracture toughness, such as high-temperature components of aero-engines.

[0022] Furthermore, the method is used to improve the microhardness of TC11 titanium alloy components. Preferably, when it is necessary to improve the hardness of TC11 titanium alloy components, a high-cycle cross-phase region cyclic heat treatment scheme is adopted: the printed part is placed at 1020℃ for 10 min, then transferred to 930℃ for 30 min, and this cycle is repeated 10 times. After air cooling to room temperature, it is then aged at 530℃ for 6 h. After this treatment, the β-stabilizing elements (Mo, Zr, Si, etc.) are more fully redistributed, the residual β-phase content is further increased, and fine secondary α-phase precipitates. The microhardness can reach 422-437 HV, which is about 9%-10% higher than that of conventional solution aging treatment (about 386-397 HV). This scheme is suitable for components with high requirements for surface wear resistance and fretting wear resistance.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention provides a method for controlling the microstructure of TC11 titanium alloy by cyclic heat treatment in LPBF additive manufacturing. Through multiple cyclic heat treatments in two temperature zones, the non-equilibrium α′ martensite in the printed microstructure of TC11 titanium alloy formed by laser powder bed melting gradually decomposes, cuts, shortens and spheroidizes by utilizing the repeated migration of α / β interfaces and the cumulative effect of phase transformation stress. This effectively solves the problems of microstructure coarsening and obvious microstructure inheritance in single annealing or solution treatment. According to the selection of T1 temperature, the present invention provides two control routes: two-phase region cycling (T1 and T2 are both located in the α+β two-phase region) can obtain fine and uniform equiaxed α+β microstructure, effectively reduce continuous grain boundary α, and improve microstructure uniformity and isotropy; cross-phase region cycling (T1 is higher than the β transformation temperature, T2 is located in the α+β two-phase region) can obtain basket-like α+β microstructure, destroy the original lath structure and promote the re-precipitation of multi-oriented α lamellae.

[0024] (2) The cyclic heat treatment microstructure control method provided by this invention is applied to the preparation of TC11 titanium alloy components. Different service performance requirements can be met by selecting different cyclic regimes. A fine and uniform equiaxed α+β microstructure can be obtained by cycling at 980 ℃-850 ℃ for 4 times in the two-phase region, which is suitable for components such as compressor disks and structural frames with high requirements for microstructure uniformity and isotropy. A basket-like α+β microstructure can be obtained by cycling at 1020 ℃-930 ℃ for 5 times in the transphase region, which is suitable for high-temperature components of aero-engines with high requirements for high-temperature creep strength, creep resistance, and fracture toughness. A microhardness of 422-437 HV can be achieved by cycling at 1020 ℃-930 ℃ in the transphase region combined with aging treatment at 530 ℃, which is suitable for components with high requirements for surface wear resistance and fretting wear resistance. This invention provides a systematic heat treatment solution for microstructure control of additive manufacturing TC11 titanium alloys. Attached Figure Description

[0025] Figure 1 The images show the metallographic structures of TC11 titanium alloy printed parts under different cyclic heat treatment regimes in Examples 1-4 of this invention, wherein: (a) the metallographic structure of Example 1 after 4 cycles of treatment at 980 ℃-850 ℃; (b) the metallographic structure of Example 2 after 4 cycles of treatment at 950 ℃-850 ℃; (c) the metallographic structure of Example 3 after 5 cycles of treatment at 1020 ℃-930 ℃; and (d) the metallographic structure of Example 4 after 10 cycles of treatment at 1020 ℃-930 ℃. Figure 2 The images show the scanning electron microscope (SEM) microstructures of TC11 titanium alloy printed parts under different cyclic heat treatment regimes in Examples 1-4 of this invention, wherein: (a) SEM microstructure of Example 1 after 4 cycles of treatment at 980 ℃-850 ℃; (b) SEM microstructure of Example 2 after 4 cycles of treatment at 950 ℃-850 ℃; (c) SEM microstructure of Example 3 after 5 cycles of treatment at 1020 ℃-930 ℃; and (d) SEM microstructure of Example 4 after 10 cycles of treatment at 1020 ℃-930 ℃. Detailed Implementation

[0026] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0027] This invention provides a method for controlling the microstructure of TC11 titanium alloy through cyclic heat treatment in LPBF additive manufacturing, comprising the following steps: Step S1: Provide a TC11 titanium alloy printed part formed by laser powder bed melting, the printed microstructure including α′ martensite.

[0028] Step S2: The heat treatment furnace is preheated to the first cycle temperature T1, and the printed part is placed in the heat treatment furnace for heat preservation, so that part or all of the α′ phase dissolves and forms the β phase; T1 is set in the α+β two-phase region, or in the transphase region above the β transition temperature.

[0029] Step S3: The other heat treatment furnace is preheated to the second cycle temperature T2. The sample is taken out from the T1 heat treatment furnace and quickly placed into the T2 heat treatment furnace and kept at the temperature. The transfer time does not exceed 1 minute, so that the β phase re-precipitates into the α phase, inducing α / β interface migration and interface diffusion. T2 is set in the α+β two-phase region, so that the re-precipitated α phase has multi-oriented nucleation and lamellar shortening conditions.

[0030] Step S4: Repeat steps S2 and S3 a total of n times, n≥2, to cut, shorten or spherize the α-lamellae through repeated phase transitions, or to form a multi-oriented, interlaced basket-like α+β tissue.

[0031] Step S5: After the cycle is completed, air cool to room temperature; optionally, age at 520-540 ℃ for about 5-7 h to promote the precipitation of fine secondary α phase and further enhance hardness.

[0032] The present invention will be further described below with reference to specific embodiments, but these are not intended to limit the scope of the invention.

[0033] Example 1 This embodiment provides a method for controlling the microstructure of cyclic heat treatment in additive manufacturing of TC11 titanium alloy, including the following steps: S1. Provide a TC11 titanium alloy printed part formed by laser powder bed melting, wherein the microstructure of the TC11 titanium alloy printed part includes α′ martensite.

[0034] S2. Preheat the heat treatment furnace to 980°C, place the TC11 titanium alloy printed part in the heat treatment furnace and keep it at that temperature for 20 minutes to decompose part of the α′ martensite structure and form the β phase.

[0035] S3. Preheat another heat treatment furnace to 850℃. Take the TC11 titanium alloy printed part after S2 from the 980℃ heat treatment furnace and quickly put it into the 850℃ heat treatment furnace for 20 minutes. The transfer time should not exceed 1 minute to allow the β phase to reprecipitate into the α phase, inducing α / β interface migration and interface diffusion.

[0036] S4. Repeat steps S2 and S3 a total of 4 times.

[0037] S5. After the cycle is completed, air cool to room temperature, take some samples directly as non-aging samples, and age the remaining samples at 530 ℃ for 6 h.

[0038] Example 2 The difference between this embodiment and embodiment 1 is that in step S2, the heat treatment furnace is preheated to 950°C (980°C in embodiment 1), while the remaining steps and parameters are the same as in embodiment 1.

[0039] Example 3 This embodiment provides a method for controlling the microstructure of cyclic heat treatment in additive manufacturing of TC11 titanium alloy, including the following steps: S1. Provide a TC11 titanium alloy printed part formed by laser powder bed melting, wherein the microstructure of the TC11 titanium alloy printed part includes α′ martensite.

[0040] S2. Preheat the heat treatment furnace to 1020℃, place the TC11 titanium alloy printed part in the heat treatment furnace and keep it at that temperature for 10 minutes to completely dissolve the α′ martensite structure and form the β phase (at this time, the temperature is higher than the β transformation temperature of the TC11 titanium alloy).

[0041] S3. Preheat another heat treatment furnace to 930℃. Take the TC11 titanium alloy printed part after S2 treatment out of the 1020℃ heat treatment furnace and quickly put it into the 930℃ heat treatment furnace for 30 minutes. The transfer time should not exceed 1 minute, so that the β phase re-precipitates into the α phase, inducing α / β interface migration and interface diffusion.

[0042] S4. Repeat steps S2 and S3 a total of 5 times.

[0043] S5. After the cycle is completed, air cool to room temperature, take some samples directly as non-aging samples, and age the remaining samples at 530 ℃ for 6 h.

[0044] Example 4 The difference between this embodiment and embodiment 3 is that the number of cycles in step S4 is 10 (5 times in embodiment 3), while the remaining steps and parameters are the same as in embodiment 3.

[0045] The Influence of Cyclic Heat Treatment on the Microstructure and Properties of TC11 Titanium Alloy in Printed State Depend on Figure 1 The metallographic images show that after four cycles of treatment at 980 ℃-850 ℃ in Example 1, the microstructure mainly consists of fine and uniform equiaxed α grains, with a small amount of short rod-shaped or slender lamellar α grains remaining locally. The continuous grain boundary α grains are significantly reduced, and the equiaxing effect is obvious. Figure 1a). After four cycles of treatment at 950 ℃-850 ℃ in Example 2, continuous coarse α-blocks or original β-grain boundary traces that were not effectively cut still existed, and the degree of equiaxation was significantly weaker than that in Example 2. Figure 1 a( Figure 1 b). In Example 3, after being treated with 5 cycles at 1020℃-930℃, the tissue exhibited a densely interwoven needle-like α-lamellae basket-like structure with diverse lamellar orientations and significant basket-like characteristics. Figure 1 c). In Example 4, after being treated with 10 cycles of 1020 ℃-930 ℃, the α-lamellae became significantly coarser, the interlamellar spacing increased, the residual β-phase content increased, and the tissue showed a trend of evolving from a basket-like structure to a coarser one. Figure 1 d).

[0046] Depend on Figure 2 The scanning electron microscope images show that after being treated at 980 ℃-850 ℃ for 4 cycles, the microstructure of Example 1 consists of fine and uniform equiaxed α grains with relatively uniform α grain size and a regular microstructure. Figure 2 a). After being treated with 4 cycles at 950℃-850℃ in Example 2, the tissue regularity was less than that of the previous method. Figure 2 a) Locally visible grain size differences ( Figure 2 b). In Example 3, after being treated 5 times at 1020 ℃-930 ℃, the α-lamellae were arranged in a single orientation and the lamellars were relatively dense. Figure 2 c). In Example 4, after being treated with 10 cycles of 1020 ℃-930 ℃, the α-lamellae exhibited an alternating distribution of two different orientations, and the lamellar width was relatively small. Figure 2 c has increased ( Figure 2 d).

[0047] comprehensive Figure 1 Metallographic structure and Figure 2 SEM microstructure observations revealed that cycling the two-phase region at 980℃-850℃ four times effectively transformed the printed α′ martensite structure into fine and uniform equiaxed α+β structure, demonstrating a significant equiaxed reconstruction effect. However, the microstructure refinement effect of cycling the two-phase region at 950℃-850℃ four times was weaker than that of the 980℃-850℃ scheme, with continuous coarse α structure still present. Cycling the cross-phase region at 1020℃-930℃ five times yielded a densely interwoven basket-like α+β structure; after ten cycles, lamellar coarsening occurred, the residual β phase increased, and the microstructure tended towards coarsening.

[0048] Furthermore, the hardness of the samples from Examples 1-4 and the control state was tested using an HV-1000A micro Vickers hardness tester. The load was 4.90 N and the holding time was 15 s. Multiple points were measured for each state and the average value was taken. The results are shown in Table 1.

[0049] Table 1

[0050] As shown in Table 1, without aging treatment: the hardness of Example 1 (980 ℃-850 ℃-4) was 310-324 HV, lower than that of the solution-treated control state (386-397 HV). This is mainly because the tissue regulation direction of biphase region cycling is equiaxed and interface optimization, and the strengthening response needs aging to be fully released. Example 2 (950 ℃-850 ℃-4) was 325-335 HV, which was basically the same as that of Example 1. Example 3 (1020 ℃-930 ℃-5) was 355-365 HV, which was significantly improved compared with Examples 1 and 2, indicating that the biphase region cycling itself already has a certain strengthening effect. Example 4 (1020 ℃-930 ℃-10) was 375-385 HV, which was the highest in the unaged group, indicating that the increase in the number of cycles promoted the redistribution of β-stabilizing elements and tissue strengthening.

[0051] After aging treatment, the hardness of each embodiment was significantly improved: the hardness of Example 1 (4 cycles at 980 ℃-850 ℃) was approximately 392-397 HV, which was basically equivalent to the solution-aged control state; the hardness of Example 2 (4 cycles at 950 ℃-850 ℃) was approximately 381-386 HV, which was lower than that of Example 1 and the solution-aged control state, indicating that the equiaxed formation and strengthening response were relatively limited at lower T1 temperatures. The hardness of Example 3 (5 cycles at 1020 ℃-930 ℃) was approximately 407-410 HV, which was significantly higher than that of the solution-aged control state, indicating that the cross-phase cycling promoted the re-precipitation of the α phase and the strengthening of the microstructure. The hardness of Example 4 (10 cycles at 1020 ℃-930 ℃) was approximately 422-437 HV, the highest value among all test conditions. This indicates that the increase in the number of cycles promoted the redistribution of β-stabilizing elements (such as Mo, Zr, Si), further increased the content of residual β phase, and precipitated fine secondary α phase, thereby obtaining the highest hardness strengthening effect.

[0052] The above results indicate that cyclic heat treatment itself has a certain strengthening effect, and the strengthening effect increases with the number of cycles; aging treatment can further significantly improve hardness on the basis of cyclic heat treatment. Based on the combined results of microstructure observation and hardness test, when the goal is to refine, homogenize, and make the α-lamellae equiaxed, it is preferable to cycle 4 times in the two-phase region at 980℃-850℃ (Example 1); when the goal is to further improve hardness, it is preferable to cycle 10 times in the transphase region at 1020℃-930℃ combined with aging treatment (Example 4), but the number of cycles needs to be controlled to avoid lamellar coarsening.

[0053] In summary, this invention addresses the challenge of controlling the non-equilibrium α′ martensite structure in the printed microstructure of laser-bed powder melt-formed TC11 titanium alloy. Through multiple cycles of heat treatment in the α+β two-phase region or across the β phase region, utilizing the repeated migration of the α / β interface and the cumulative effect of phase transformation stress, it achieves controllable reconstruction of the printed microstructure into a fine, uniform, equiaxed α+β structure or a basket-like α+β structure. Furthermore, the control route can be flexibly selected according to target service requirements, and hardness can be further improved through aging treatment. This invention provides a systematic heat treatment solution for microstructure control and performance optimization of additively manufactured TC11 titanium alloys.

[0054] The above are merely preferred embodiments of the present invention and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should recognize that any equivalent substitutions and obvious changes made based on the content of this specification should be included within the protection scope of the present invention.

Claims

1. A method for controlling the microstructure of TC11 titanium alloy through cyclic heat treatment in LPBF additive manufacturing, characterized in that, Includes the following steps: S1. Provide a TC11 titanium alloy printed part formed by laser powder bed melting, wherein the microstructure of the TC11 titanium alloy printed part includes α′ martensite; S2. The TC11 titanium alloy printed part is placed at a first temperature T1 and kept at that temperature to cause some or all of the α′ martensite to decompose and form the β phase. S3. The TC11 titanium alloy printed part after S2 is placed at a second temperature T2 and kept at that temperature to allow the β phase to re-precipitate into the α phase. S4. Repeat steps S2 and S3 a total of n times, where n≥2; S5. Air cool the TC11 titanium alloy printed part after step S4 to room temperature. Wherein, T1 > T2, T2 is within the α+β dual-phase temperature range of TC11 titanium alloy, and T1 is within the α+β dual-phase temperature range of TC11 titanium alloy or higher than the β transformation temperature of TC11 titanium alloy.

2. The method for regulating microstructure during cyclic heat treatment according to claim 1, characterized in that, The temperature T1 is 950-990℃, and the holding time is 10-30 min; the temperature T2 is 830-870℃, and the holding time is 10-30 min; the n is 3-5.

3. The method for regulating microstructure during cyclic heat treatment according to claim 1, characterized in that, The temperature T1 is 1010-1030℃, and the holding time is 5-15 min; the temperature T2 is 920-940℃, and the holding time is 20-40 min; the temperature n is 4-10.

4. The method for controlling microstructure during cyclic heat treatment according to claim 1, characterized in that, Steps S2 and S3 are performed in different heating furnaces; in step S3, the TC11 titanium alloy printed part after step S2 is transferred from the heating furnace at the first temperature T1 to another heating furnace that has been preheated to the second temperature T2, and the transfer time does not exceed 1 minute.

5. The method for regulating microstructure during cyclic heat treatment according to claim 1, characterized in that, Steps S2 and S3 are performed in an air atmosphere.

6. The method for controlling the microstructure during cyclic heat treatment according to claim 1, characterized in that, Step S5 also includes: aging the TC11 titanium alloy printed part that has been air-cooled to room temperature, with an aging temperature of 520-540 ℃ and a time of 5-7 hours.

7. The application of the cyclic heat treatment microstructure control method according to any one of claims 1-6 in the preparation of TC11 titanium alloy components.

8. The application according to claim 7, characterized in that, The cyclic heat treatment microstructure control method is used to transform the α′ martensite in the TC11 titanium alloy printed part into a fine and uniform equiaxed α+β microstructure.

9. The application according to claim 7, characterized in that, The cyclic heat treatment microstructure control method is used to transform α′ martensite in TC11 titanium alloy printed parts into basket-like α+β microstructure.

10. The application according to claim 7, characterized in that, The cyclic heat treatment microstructure control method is used to improve the hardness of TC11 titanium alloy components.